The Jihadist Preachers of the End Times - Meschonnic, Henri (Edinburgh University Press, 2019)
Focusing on apocalyptic manifestations found in ISIS propaganda, this book situates the group's agenda in the broader framework of contemporary Muslim thought and explains key topics in millennial thinking within the spiritual context of modern Islamic apocalypticism.